2016
DOI: 10.1021/acs.jnatprod.6b00142
|View full text |Cite
|
Sign up to set email alerts
|

Taste-Guided Isolation of Bitter Lignans from Quercus petraea and Their Identification in Wine

Abstract: Quercoresinosides A and B (1 and 2), two new lignans, were isolated from a toasted Quercus petraea heartwood extract along with a known compound, 3-methoxy-4-hydroxyphenol 1-O-β-d-(6'-O-galloyl)glucopyranoside (3). The purification protocol was based on a taste-guided approach that sought to reveal new bitter compounds released from oak wood into wines and spirits. HRMS and NMR data were used to establish that compounds 1 and 2 are lignan derivatives bearing a glucosyl unit and a galloyl unit at the same posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Baldwin et al [13] found low levels of vanillin (ranging from 0.6 to 1. The most recent works [6,56,105] were based on a factorial design using the same wine distillate from the Lourinhã region (produced by Adega Cooperativa da Lourinhã) aged over a four-year period in barrels made from the following kinds of wood: Limousin oak (Q. robur L.) and Allier oak (Q. sessiliflora Salisb.) from French forests; American oak (mixture of Q. alba L./Q.…”
Section: Phenolic Compositionmentioning
confidence: 99%
See 4 more Smart Citations
“…Baldwin et al [13] found low levels of vanillin (ranging from 0.6 to 1. The most recent works [6,56,105] were based on a factorial design using the same wine distillate from the Lourinhã region (produced by Adega Cooperativa da Lourinhã) aged over a four-year period in barrels made from the following kinds of wood: Limousin oak (Q. robur L.) and Allier oak (Q. sessiliflora Salisb.) from French forests; American oak (mixture of Q. alba L./Q.…”
Section: Phenolic Compositionmentioning
confidence: 99%
“…Portuguese oak wood promoted intermediate enrichment, with the highest level of sinapaldehyde, while the other kinds of oak had a weaker performance. However, the richness of coumarins associated with the American oak should be stressed, because these compounds can act as chemical markers of this kind of wood [56,95]. Comparing the results of the oldest and most recent works, important differences in the concentrations of phenolic aldehydes, phenolic acids and scopoletin in wine brandies aged in French oak wood and American oak wood are observed.…”
Section: Phenolic Compositionmentioning
confidence: 99%
See 3 more Smart Citations